Vertical Organic Electrochemical Transistors and Electronics for Low Amplitude Micro‐Organ Signals. Issue 8 (22nd January 2022) - Abarkan, Myriam; Pirog, Antoine; Mafilaza, Donnie; Pathak, Gaurav; N'Kaoua, Gilles; Puginier, Emilie; O'Connor, Rodney; Raoux, Matthieu; Donahue, Mary J.; Renaud, Sylvie; Lang, Jochen
Abstract: Electrical signals are fundamental to key biological events such as brain activity, heartbeat, or vital hormone secretion. Their capture and analysis provide insight into cell or organ physiology and a number of bioelectronic medical devices aim to improve signal acquisition. Organic electrochemical transistors (OECT) have proven their capacity to capture neuronal and cardiac signals with high fidelity and amplification. Vertical PEDOT:PSS‐based OECTs (vOECTs) further enhance signal amplification and device density but have not been characterized in biological applications. An electronic board with individually tuneable transistor biases overcomes fabrication induced heterogeneity in device metrics and allows quantitative biological experiments. Careful exploration of vOECT electric parameters defines voltage biases compatible with reliable transistor function in biological experiments and provides useful maximal transconductance values without influencing cellular signal generation or propagation. This permits successful application in monitoring micro‐organs of prime importance in diabetes, the endocrine pancreatic islets, which are known for their far smaller signal amplitudes as compared to neurons or heart cells. Moreover, vOECTs capture their single‐cell action potentials and multicellular slow potentials reflecting micro‐organ organizations as well as their modulation by the physiological stimulator glucose. This opens the possibility to use OECTs in new biomedical fields well beyond their classical applications. Abstract : Islet micro‐organs are of prime importance in health and diabetes but their electrical signals are far smaller than those of brain or heart. High signal amplification by vertical organic electrochemical transistors (vOECTs) combined with a tunable electronic board allows reliable quantitative capture of glucose‐dependent single‐cell and multicellular islet activities. This opens new biomedical applications for OECTs beyond their classical use.